Outcome of Different Approaches to Reduce Urinary Tract Infection in Patients With Spinal Cord Lesions: A Systematic Review. (November 2020) - Chang, Shih-Chung; Zeng, Shengwei; Tsai, Su-Ju
Abstract : Abstract: Neurogenic bladder disorders are common among patients with spinal cord lesions, which often result in upper and lower urinary tract complications. Urinary tract infection has remained the most frequent type of infection in this population. Our aim is to review systematically the literature on the outcome of different intervention methods to reduce urinary tract infection incidence. A literature search was conducted in the database of Medline, PubMed, Embase, and Scopus. After screening 1559 articles, 42 were included in this review. The intervention methods can be categorized into the four following groups: (1) indwelling catheterization and intermittent catheterization, (2) medications, (3) surgery, and (4) others. Intermittent catheterization is still the most recommended treatment for persons with spinal cord lesions. Hydrophilic catheters are more suitable for adults than children because of complex handling. Bladder management with spontaneous voiding is initially considered for infants and toddlers with spina bifida. Antibiotics treatment should be based on the results of urine cultures. Shortening the course of antibiotics treatment can reduce its adverse effects but may increase urinary tract infection recurrence. Because botulinum toxin injections and bladder surgery can improve urodynamic function, both are conducive toward lowering urinary tract infection incidence. Abstract : Supplemental digital content is available in the text.